The Relationship of Technology Advancement, Company Management, and Manager Knowledge on the Effectiveness of Accounting Information Systems - Eel Susilowati; R Rofi'ah; Silvia Avira (IJISTECH (International Journal of Information System and Technology), 2022)
The background of this research is how to find the variables related to the accounting information system in a company, by knowing these variables, it can be seen which variables significantly affect the accounting information date variable. In this study, the method applied in this research is the literature review method and uses a survey tool to 100 employees at a company, with a survey conducted, it can be seen the data in the field, so that the data can be proven validly so that the data can be used now or in the future. The problem raised in this study is that there are three hypotheses, namely the first hypothesis is there a relationship between advanced technology and the effectiveness of the accounting information system, the second hypothesis is there a relationship between company management and the effectiveness of the accounting information system. The third hypothesis is there a relationship between managers' knowledge and the effectiveness of accounting information systems. The purpose of this study is how to find out the variables that are significantly involved in the effectiveness of the accounting information system variable which can be seen from the independent variables directed at this research. The independent variable is the sophistication of the company's management technology from the manager. Significant in influencing the effectiveness of the accounting information system